Strategi IMC Schoters: pada Event Open House dan Roadshow untuk Meningkatkan Penjualan dan Jangkauan Pasar - Octaviani; Oky Oxcygentri; Khairul Arief Rahman (KOMVERSAL, 2024)
The development of the business world is currently experiencing rapid progress which has given rise to many start-up companies, especially in the field of Edutch. Schoters, as one of the start-up companies, implement an effective marketing communication strategy through organizing events such as open house and roadshow events to expand consumers and increase sales.Tthe role of events in promotional activities is considered effective because it can help make it easier for companies to spread their service products. This study aims to determine the marketing communication strategy used by schoters in promoting open house and roadshow events at schoters through an integrated marketing communication (IMC) strategy. Qualitative research method with a descriptive approach. Data collection through primary and secondary data, namely through observation, interviews, documentation and literature studies. The results showed that the marketing communication strategy implemented by Schoters was effective in expanding the market and increasing sales. The IMC strategies used include (sales promotion) through discounts and special offers, which are carried out through direct marketing and personal selling and using (advertising) digitally through organic and paid media and non-digital through KRL brochures and posters.